Предмет: Алгебра,
автор: Natan12345
Упростите выражение (2z-3)^2-3z^2-9
Ответы
Автор ответа:
1
Ответ:
z(z-12)
Объяснение:
Автор ответа:
0
Ответ:
z^2 - 12z
Объяснение:
(2z - 3)^2 - 3z^2 - 9 =
(4z^2 - 12z + 9) - 3z^2 - 9 =
4z^2 - 12z + 9 - 3z^2 - 9 =
4z^2 - 12z - 3z^2 =
z^2 - 12z
Похожие вопросы
Предмет: Математика,
автор: demchenkoanna362
Предмет: Математика,
автор: renfill
Предмет: Українська література,
автор: stankevich79
Предмет: Математика,
автор: Аноним
Предмет: История,
автор: Karajmanyura